Red blood cell variables in children and adolescents regarding the age and sex - Pluncević Gligoroska J.; Gontarev S.; Dejanova B.; Todorovska L.; Shukova Stojmanovska D.; Manchevska S. (2019). (Iranian Journal of Public Health, 2019)
Background: This study aimed to assess the basic red blood cell variables and hematological indices in chil- dren and adolescents and analyze the differences regarding age and sex. Methods: Overall, 320 young participants, age 8 to 18 yr, were enrolled at Laboratory of Sport’s Medicine, Medical Faculty, Skopje, Macedonia in 2016. Capillary blood samples were drawn and following hematologic parameters were measured: the red blood cell count (RBC), hemoglobin concentration (Hb), hematocrit level (Hct) and hematological indexes: mean corpuscular volume (MCV), mean hemoglobin concentration (MCH), mean corpuscular hemoglobin concentration (MCHC) and red cell distribution width (RDW). Results: RBC variables in male group showed high statistical level of significance between age different groups (P=0.001) for all studied parameters except MCHC (P=0.423) and RDW (P=0.174). ANOVA test and multi- variate tests in female group showed that there was no significant difference for all hematological parameters between age different groups. Regarding the sex differences, male participants had significantly higher red blood count (P<0.001), hemoglobin content (P<0.001) and hematocrit (P<0.001). Conclusion: Hematological parameters in adolescent as inhomogeneous population are not quantified suffi- ciently, especially hematological indices. RBC variables, regardless of the age, differ very much between male and female examinees, in favor of the male examinees. Hematological indices were insignificantly higher in males. Regarding the age of examinees, RBC variables showed significant inter-groups differences only within male adolescents. While with girls, ages span 8 to 18 yr, we did not find significant differences for most of the hematological variables.
Keywords: Red blood cells; Hemoglobin; Hematological indices; Adolescent; Anemia